A formação inicial de professores de ciências e biologia: uma análise a partir da visão de licenciandos de uma universidade pública - Pitolli, Alexandra Marselha Siqueira (2014)
This thesis falls within the scope of the investigations on the influence of the National Curriculum Guidelines (DCN) in teacher education. This is a qualitative researchin which an analysis of the insertion is performed in the curriculum guidelines, relating to practical and research components in the curriculum from the assessment that the licensees of a Biological Sciences course of a Federal University, in São Paulo, performed on their training and the analysis of the Pedagogical Project Course for identifying the agreements and disputes involved in its production. One goal was to understand the emphasis on practical and research in the initial training mainly from the perception of the participants.The data obtained through questionnaires, interviews and document analysis were analyzed using the methodology of Análise Textual Discursiva. Regarding the assessment conducted by undergraduates it is possible to understand that they attribute to the practice - citing stages and disciplines that in the University are responsible for the discussion and reflection on events experienced by them in elementary school - as a salient factor to be closer to the future profession and as an element that enabled to desire the entrance into the teaching profession. They attach to the discipline of Practice and Research in Biological Sciences (PPECB) a fundamental role as a tool to bring them closer to education and research in science education and biology and how a knowledge and skill that adds value to their initial training and arouses interest in learning more about the area. In the analysis of the pedagogical project of the course, it was possible to understand the agreements and adjustments made within the institution in order that the degree course is defined as configured with the DCN and by the knowledge produced in the research field in curriculum and teacher training. In the curriculum of the degree course - with its own identity - it is possible to note the pursuit of articulation of different practices in which undergraduates may mean your training and have the perception of the complexity of the profession. This occurs through the development of reading, analysis, discussion and collective practice based on reflective processes in university activities. The link between theory and practice in the vaunted DCN is promoted when it confronts the practical knowledge to the translated theory into the curriculum of the course. This proposition is made possible with practice permeating the entire period of training, associating the moments of experience in schools experience with the course content.